DESIGNING FORECASTING SYSTEM NUMBER OF FOREIGN TOURIST VISITS - Miftahul Jannah (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
This research is designing a system of forecasting the number of foreign tourists in North Sumatra Province with a computerized system. Tourism is one of the important roles in the economic sector in Indonesia. The role of tourists both local and foreign influential in the development of the world of tourism in North Sumatra. But in fact the problem of transportation, preparation of services (shelter) and road density are often the main obstacles if there is an increase in the number of visitors coming to North Sumatra. To avoid the problems that have been discussed above, a system is needed to predict the number of tourists. Simple Linear regression is the method chosen in the process of planning and the system is built in the Visual Studio 2010 programming language and for data storage used by Microsoft Access. The results of the study are the forecasting system for the number of foreign tourists in North Sumatra based on the historical data of the last 10 years showing that foreign tourists who will visit in January 2016 in North Sumatra are 16,937 people.